Tipos e níveis de cobertura de solo e seu efeito na eficiência da irrigação localizada de coqueiro-anão (Cocos nucifera L.) - Souza, Erick Alexandre Doria (2020)
The coconut tree, a dwarf ecotype, has shown continuous growth in its cultivation area, with its production mainly destined to obtain “coconut water”, whose consumption has been increasing in Brazil and in the world and making our country the largest world producer. The dwarf coconut tree, associated with micro-sprinkler irrigation, has a better productive performance and an early start of production, compared to other cultivars. This cultivation is characterized by high water consumption, which increases production costs and demands the conduction of research in order to maximize the efficiency of the use of this input. In this way, this work was established a field of cultivation of dwarf coconut tree in production phase and irrigated by a micro sprinkler type irrigation system and aimed to evaluate the effect of mulch on the retention of applied irrigation water and the pattern of soil moistening, in cultivation of micro-irrigated dwarf coconut. For that, three conditions were evaluated: soil without cover, with cover using raffia and with cover using coconut leaves, the latter with the formation of cover with 10, 30 and 50 leaves; under two irrigation doses, 50 and 100 L plant-1 day-1, which were assessed for water interception level and wetting profile from irrigation. To evaluate the soil wetting profile, only the mulch cover formed by 30 leaves, in addition to the raffia and soil treatments without cover were evaluated. The experimental design used was that of randomized blocks, consisting of eight treatments and three repetitions, with ANAVA being performed for the factor “level of retention”. To obtain the soil moistening profile, humidity probes were used, based on the principle of reflectometry in the frequency domain - FDR. It was concluded that among the materials used as cover, the raffia presented a lower retention index in relation to the mulch with leaves; and among the treatments that used leaves, there was an inverse relationship between retention level and irrigation dose and a direct relationship between retention level and number of leaves used in the cover. The soil wetting profile was influenced by the type of soil cover, and the straw of coconut leaves was the one that resulted in the highest average humidity of the profile.